Metal additive manufacturing of conformal cooling channels in plastic injection molds with high number of design variables - Kanbur, Baris Burak (2023)
Metal additive manufacturing (MAM) is an effective way to fabricate conformal cooling channels (CCCs), which follow the curves of the plastic product in the mold body of the plastic injection. CCCs have free-curved pathways thanks to the design & manufacturing flexibilities of the MAM process so that they can achieve better cooling performance with shorter cooling time and smaller temperature non-uniformity. On the other hand, the flexibilities of the MAM process bring multiple options for design variables and the high number of design variables make the final design of CCCs complex, high-cost, and time-consuming. Considering this challenge, this study presents the entire process of MAM of CCCs for a target product with eight different design variables, which makes it a product with a high number of design variables, from the initial design to the on-site manufacturing including the steps of computer-aided design & simulations, metamodel, multiobjective optimization, and the printing quality monitoring. The target product has three main objectives that are i) the temperature difference between the maximum and minimum values at the internal wall of the mold, ii) maximum temperature in the mold body, and iii) pressure drop. The optimized product is then printed via direct metal laser sintering (DMLS) machine and the quality check is done via X-ray computed tomography.